Pengaruh Manajemen Laba Efisien Terhadap Nilai Perusahaan Dengan Rasio Profitabilitas - Dedie Wijaya (Universitas Prasetiya Mulya, 2017)
The purpose of this research is to estimate whether Efficient Earnings Management will affect the company’s value by using Accounting Performance Analysis ratio as a moderating variable. The presence of Earnings Management misleads investors into producing an incorrect fundamental analysis of a company which effects on the company’s value. The methodological tools to estimate earnings management are Kasznik models (1999) which refer to Siregar and Utama’s research (2008). This research-based on research toward a company that is listed in Jakarta Stock Exchange from 2000 to 2014. The results of this research are proven that there are a positive correl Management and Company’s Values, therefore the presence of the Efficient Earning Management will increase the value of a company. Keywords: Efficient Earnings Management, Company’s Value, Accounting Performance Analysis https://doi.org/10.21632/saki.1.1.54-71